Electro-Monorails- An Alternative Operating System for Deep Mining - Burke, PA; Chanda, EK (Deep Mining 2007: Proceedings of the Fourth International Seminar on Deep and High Stress Mining, 2007)
The need to develop innovative responses to the challenges posed by mining at depths below 600 m has been recognised. The large excavations associated with current underground bulk mining practices are unlikely to be geotechnically and economically sustainable in these conditions. The heat load and airborne exhaust contaminants emitted by large diesel engines working at these depths can create unacceptable demands on mine ventilation systems resulting in substandard working conditions. This paper proposes the adaptation of existing monorail technology using continuous conductor technology to provide competitive haulage rates in substantially smaller access excavations at steeper grade that is currently achievable. It is additionally proposed that a suite of equipment can readily be sourced to enable development of these excavations supported by the monorail system. As a capital cost optimising approach it is suggested that the electrical conductors associated with the monorail form the second level electrical reticulation for the mine workings.